The Execution Rights Of Dependents Online - I Nyoman Semadiartha; I Nyoman Sujana; I Ketut Widia (Jurnal Hukum Prasada, 2020)
The study was motivated by the increasingly influential technology against the executions carried out by the Bank as an alternative to the completion of bad debt. Online auction based on article 6, UUHT is the executable can cause conflict parate norms, because the existence of regulations implementing the Government-level, as article 26 UUHT, associated with article 7 (1) of law No. 12 of 2011. Parate executions required by Court Fiat. The theory is a theory of hierarchi theory of norms, legal certainty and the theory of legal protection. This study aims to examine the dependent object execution rights in the settlement effort as the execution parate bad debt at The Rural of Banks and to describe the legal protection for the winner of the auction as a result of the implementation of the execution rights of dependents. This type of research and the approach is normative, legal research with approach of legislation and cases. The result of this study gave conclusion on the dependent right execution parate conducted an online lender as an alternative to the last settlement of bad debt, for quick and efficient. Auction winner gets legal protection internally, because the lender makes a deal with the auction winner that the auction is legal transactions such as selling in General. External legal protection, the State provides legal protection to all parties in the execution of rights to dependents.